Cellular factor YY1 downregulates the human papillomavirus 16 E6/E7 promoter, P97, in vivo and in vitro from a negative element overlapping the transcription-initiation site - Lace, Michael J.; Yamakawa, Yasushi; Ushikai, Masato; Anson, James R.; Haugen, Thomas H.; Turek, Lubomir P. (Journal of General Virology, 2009)
Cellular factors that bind to cis sequences in the human papillomavirus 16 (HPV-16) upstream regulatory region (URR) positively and negatively regulate the viral E6 and E7 oncogene promoter, P97. DNase I footprinting has revealed the binding of cellular proteins to two previously undetected cis elements overlapping and 3′ of the transcription-initiation site of the P97 promoter. Mutations within homologous motifs found in both of these cis elements abolished their negative function in vivo and the binding of the same cellular complex in vitro. This factor was identified as YY1 by complex mobility and binding specificity in comparison with vaccinia virus-expressed, purified recombinant YY1 protein and by antigenic reactivity with YY1 antisera. Cis mutations in the ‘initiator’ YY1 site activated the P97 promoter in vivo and in vitro. P97 was also activated threefold in vitro by depletion of endogenous YY1 with wild-type, but not mutant, YY1 oligonucleotides from the IgH kappa E3′ enhancer. Furthermore, increasing concentrations of exogenous, purified recombinant YY1 repressed wild-type P97 transcript levels by up to threefold, but did not influence the P97 promoter mutated in the ‘initiator’ YY1 site. Thus, the promoter-proximal YY1 site was not necessary for correct transcription initiation at the P97 promoter, but was found to be required for downregulation of P97 transcription in vivo and in vitro. In contrast to other viral and cellular promoters, where YY1 is thought to function as a positive transcription-‘initiator’ factor, HPV-16 P97 transcription is downregulated by YY1 from a critical motif overlapping the transcription start site.